Ultrafine Cellulose Nanofiber‐Assisted Physical and Chemical Cross‐Linking of MXene Sheets for Electromagnetic Interference Shielding. Issue 12 (20th October 2021) - Wu, Na; Zeng, Zhihui; Kummer, Nico; Han, Daxin; Zenobi, Renato; Nyström, Gustav
Abstract: Transition metal carbides and nitrides (MXenes) have shown great potential for constructing thin, high‐performance electromagnetic interference (EMI) shields. The challenges with these materials involve the weak interfacial interactions of MXenes, which results in inferior mechanical properties and structure of the MXene films and a conductivity/EMI shielding performance decay related to the poor MXene oxidation stability. Numerous efforts have been devoted to improving the mechanical properties or oxidation stability of the films, which always comes at the expense of EMI shielding performance. Here, ultrafine (≈1.4 nm) cellulose nanofibers are employed to achieve physical and chemical dual cross‐linking of MXene (PC‐MXene) nanosheets. The procedure involves drying of flexible and highly conductive PC‐MXene films at ambient pressure and is energy‐efficient and scalable. Compared to the MXene films, the PC‐MXene films show significantly improved mechanical strength, hydrophobicity, oxidation stability, and are waterproof, without compromising the excellent EMI shielding effectiveness (SE). Moreover, the freestanding PC‐MXene films reach a thickness of merely 0.9 µm and exhibit a high SE of 33.3 dB, which cannot be achieved by pure MXene films. This leads to ultrahigh thickness‐specific SE and surface‐specific SE values of 37 000 dB mm −1 and 148 000 dB cm 2  g −1 respectively, significantly surpassing those of previously reported MXene‐based films. Abstract : Ultrafine cellulose nanofibers are employed to assist in a physical and chemical cross‐linking treatment of MXene nanosheets. This leads to the preparation of the dual cross‐linked MXene‐based composite films with significantly enhanced mechanical performance, efficient water resistance, improved oxidation stability, and excellent electromagnetic interference shielding performance.